ANALISIS PERBEDAAN TINGKAT PEMAHAMAN MAHASISWA AKUNTANSI TERHADAP MATA KULIAH AUDITING 1 (Studi Empiris pada Mahasiswa Program Studi Akuntansi S 1 Universitas Bengkulu, Universitas Muhammadiyah Bengkulu, dan Universitas Terbuka - UPBJJ Bengkulu) - Kresnawati, Kresnawati; Fachruzzaman, Fachruzzaman; Suranta, Eddy (UNIB Press, 2013)
Auditing 1 is a subject which is given to students of accounting as one of the subjects of expertise. The purpose of this course that students understand about the audit and other assurance services in accordance with the conditions, the environment and business practices, laws and standards in Indonesia. The purpose of this study is to prove and analyze the understanding that there is a material difference between auditing 1 students of Accounting University of Bengkulu (UNIB) and students of Universitas Muhammadiyah Bengkulu Accounting (UMB), between students of UNIB and Student Accounting Accounting Study Program-UPBJJ Bengkulu Open University, as well as between students of UMB Accounting and Accounting students of UTUPBJJ Bengkulu. This study uses primary data, and analyzed using the Independent Sample T Test. Based on calculations in mind that the first hypothesis and the second and third hypotheses t value is greater than the table t and significant, so that Ha is accepted.